Critical illness-related corticosteroid insufficiency (CIRCI) in paediatric patients: a diagnostic and therapeutic challenge - Letteria Anna Morabito; Domenico Corica; Giorgia Pepe; Alessandra Li Pomi; Tommaso Aversa; Malgorzata Gabriela Wasniewska (BMC, 2024)
Abstract Critical illness-related corticosteroid insufficiency or CIRCI is characterized by acute and life-threatening disfunction of hypothalamic-pituitary-adrenal (HPA) axis observed among intensive care unit- staying patients. It is associated with increased circulating levels of biological markers of inflammation and coagulation, morbidity, length of ICU stay, and mortality. Several mechanisms are involved in CIRCI pathogenesis: reduced CRH-stimulated ACTH release, peripheral resistance to glucocorticoids, altered cortisol synthesis, impaired cortisol-free fraction and bioavailability. Diagnostic and therapeutic management of this condition in children is still debated, probably because of the lack of agreement among intensive care specialists and endocrinologists regarding diagnostic criteria and prevalence of CIRCI in paediatric age. In the present narrative review, we focused on definition of CIRCI in paediatric age and we advise on how to diagnose and treat this poorly understood condition, based on current literature data.